(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يهدف البحث إلى معرفة درجة ممارسة مديري التعليم الأساسي في مدينة دمشق لمعايير إدارة التغيير وكذلك لمعرفة تأثير المتغيرات المستقلة(الجنس / العمر/ الحلقة التعليمية/ الخبرة/ المؤهل العلمي). وقد اعتمد البحث على الاستبيان كأداة رئيسة في الإجابة عن الأسئلة والتحقق من فرضياته، تم تطبيق الاستبيان على عينة مؤلفة من 200 معلماً ومعلمة في مدارس التعليم الأساسي بدمشق، وتم التوصل إلى عدة نتائج هي: 1-إن درجة ممارسة المديرين في مدارس التعليم الأساسي بمدينة دمشق لمعايير إدارة التغيير كانت جيدة. سواء بصورة كلية أو على مستوى كل معيار من المعايير. 2-لم يكن لمتغير الجنس تأثير ذو دلالة إحصائية في استجابات أفراد العينة، في حين أثر متغير الحلقة التعليمية في استجابات أفراد العينة، وكان التأثير لصالح الحلقة الثانية. كذلك أثر متغير الخبرة في استجابات أفراد العينة، وكان التأثير لصالح المجموعة الأكثر خبرة. كما أثر متغير العمر في استجابات أفراد العينة، وكان التأثير لصالح المجموعة الأكثر عمراً. وأثر أيضاً متغير المؤهل العلمي في استجابات أفراد العينة، وكان التأثير لصالح المجموعة الأكثر تأهيلاً. This research aims at recognizing the degree of change management standards and the effect of independent variables (sex, age, studying cycle, experience and scientific qualification). The research depended on a questionnaire as a main instrument to answer its questions and verify its hypotheses. The questionnaire was applied on a sample of (200) male and female teachers in the schools of basic education in Damascus. The research reached the following results: The degree of principals’ practices of change management standards in the basic education schools in Damascus is good whether as a whole or at the level of each standard. There was no statistical difference of significance of the gender variable (male and female). And there were statistical differences of significance of the set variables in favor of the second one. There were statistical differences of significance of the experience variable in favor of the most experienced group (10 years experience and more) There was a statistical difference of significance of the age variable in favor of those who are the oldest (40 years old and more). There was a statistical difference of significance of the scientific qualification variable in favor of the most scientific qualification group.